A Machine Learning Approach to Monitor the Emergence of Late Intrauterine Growth Restriction - Pini, Nicolò; Lucchini, Maristella; Esposito, Giuseppina; Tagliaferri, Salvatore; Campanile, Marta; Magenes, Giovanni; Signorini, Maria G. (Frontiers in Artificial Intelligence, 2021)
Late Intrauterine Growth Restriction (IUGR) is a fetal pathological condition characterized by chronic hypoxia secondary to placental insufficiency, resulting in an abnormal rate of fetal growth. This pathology has been associated with increased fetal and neonatal morbidity and mortality. In standard clinical practice, Late IUGR diagnosis can only be suspected in the third trimester and ultimately confirmed at birth. This study presents a radial basis function support vector machines (RBF-SVM) classification based on quantitative features extracted from fetal heart rate (FHR) signals acquired using routine cardiotocography (CTG) in a population of 160 healthy and 102 Late IUGR fetuses. First, the individual performance of each time, frequency and nonlinear feature was tested. To improve the unsatisfactory results of univariate analysis we firstly adopted a recursive feature elimination approach to select the best subset of FHR-based parameters contributing to the discrimination of healthy versus Late IUGR fetuses. A fine tuning of the RBF-SVM model parameters resulted in a satisfactory classification performance in the training set (accuracy 0.93, sensitivity 0.93, specificity 0.84). Comparable results were obtained when applying the model on a totally independent testing set. This investigation supports the use of a multivariate approach for the in-utero identification of Late IUGR condition based on quantitative FHR features encompassing different domains. The proposed model allows to describe the relationships among features beyond the traditional linear approaches, thus improving the classification performance. This framework has the potential to be proposed as a screening tool for the identification of Late IUGR fetuses.